OUTCOME OF BALLOON PULMONIC VALVULOPLASTY WITH 18 MONTHS FOLLOW UP - Cheragh, H; Hassan, Mahmood ul; Hafizullah, Mohammad; Gul, Adnan Mehmood (Journal of Ayub Medical College Abbottabad, 2009)
Objective: To determine the immediate and intermediate term outcome of balloon pulmonic valvuloplasty by echocardiography. Methods: This study was conducted in the Department of Cardiology Postgraduate Medical Institute Lady Reading Hospital (LRH), Peshawar from July 1999 to January 2003. Patients with severe pulmonic valve stenosis who underwent balloon pulmonic valvuloplasty during this period were included in the study. Forty Patients fulfilling the study inclusion criteria were followed up to 18 months by two dimensional and Doppler echocardiographic examinations at 6 months interval. Patients with dysplastic valve leaflets or for whom 18 months follow up data was not available were excluded from the study. Echocardiographic data was collected prospectively. Echocardiographic hemodynamic data was analysed initially and at all three follow up visits, using descriptive statistics and paired t-test. Results: Total 64 balloon pulmonic valvuloplasty procedures were performed during this period. Forty patients fulfilled the study inclusion criteria and the remaining 24 patients were excluded from the study. Mean age of the patients was 13.05±8.22 years, ranging from 1-33 years. Pre-peak pulmonic valve gradient reduced from 100.9±29.20 mmHg to 31.38±15.99 mmHg (p<0.0001) immediately after balloon pulmonic valvuloplasty. Pulmonic valve gradient at day 1 (31.38±15.99) reduced significantly at 18 months (18.88±10.24) (p<0.0001). Complication encountered during the procedure was transient ventricular tachycardia or multiple premature ventricular contractions. Conclusion: Balloon pulmonic valvuloplasty is safe and effective in reducing pulmonic valve gradient acutely and the benefit persists till 18 months. Further fall in pulmonic valve gradient is seen in intermediate term follow up. Keywords: Pulmonic valve stenosis, balloon pulmonic valvuloplasty